ANALYSES OF RESPONSE FOR PRODUCTIVITY OF SMALLHOLDER COCOA PLANTATION IN CENTRAL SULAWESI INDONESIA: AN AGROECOSYSTEM APRROACH - Yantu, M. R.; Yunus, Moh.; Sisfahyuni, Sisfahyuni; Bustami, Mirni Ulfa (Journal of Agroecology, 2015)
Central Sulawesi is the first rank of cocoa beans supplier in Indonesia. Almost 99% of cocoa plantations in this province are smallholder. Unfortunately, farmers have been converted their cocoa plantation to others plantation such as oil palm and coffee plantations. It was caused by continuous decreasing of productivity of the plantation since attack of pest and disease. Thus, productivity of cocoa plantation needs important intention. However, productivity is constrained by the environment capacities. The aim of this study is to analyze response of productivity for smallholders cocoa plantation based on the agro-ecosystem criteria, particularly productivity. Analyses method is descriptive and econometric model. Data were time series data from 2000 to 2011. The secondary data included production of cocoa beans, size area of cocoa plantation, price of cocoa and coffee beans, averages of fertilizers price, averages of pesticides price, and wages for agricultural labor in rural area. The study shows all of independent variables, except pesticide price significantly influence the dependent variable. Thus, all production factors prices, except pesticide price significantly influence the productivity. It means that the productivity of smallholder cocoa plantation is possibly to be elevated. The study recommends (i) tightening in controlling for policy of ceiling price of production factors; (ii) developing program of extensification for cocoa plantation; (iii) continuation of study in estimating for efficiency of production factors from an organic and organic; and (iv) analyzing for the other criteria of agro-ecosystem in performing of cocoa plantation.